A proposed early childhood education program for the rural areas in the Philippines - Van der Veen, Concepcion Lomibao 1950- (1977)
The study looked into the status of early childhood education programs through the nursery-kindergarten project of the National Federation of Women's Clubs (NFWC). Some of the findings on the NFWC were:(1) the objectives were basically universal in nature; (2) the constraints were mostly financial; (3) the teaching strategies were mostly teacher-directed with hardly any provision for individual differences; and (4) program evaluation was hardly evident and there was only one supervisor for the more than 300 NFWC classes.
Appendices: leaves 211-225
Bibliography: leaves 201-210
Thesis (M.Ed.)--University of the Philippines, Quezon City
Typescript.
Vita
Keywords: Education, Preschool -- Philippines; Education, Rural -- Philippines